Passive margin sedimentation on Costa Rica's Nortb Caribbean coastal plain, Rio Colorado - Parkinson, Randall W. (1998)
Geomorphic, sedimentologic. and stratigraphic data obtained from the north Caribbean region of Costa Rica suggests Rio Colorado is a wave-dominated delta whicth has formed along a passive continental margin. This coastal setting is significantly different from tile: south Caribbean and Pacific coastlines, which display geomorphic and lithologic features indicative of seismically active continental margins. The distinct aseismic history and passive margin geomorphology of the north Caribbean coastal plain appears to be controlled by the presence of tectonic features (i.e.,East Nicoya Fracture Zone) which decouple the region from adjacent, tectonically active areas. Although the data collected during this pilot study, including two radiocarbon dates from the base of surficial wetforest and palm swamp sediment. were not sufficient to documentrelative sea-level change, they do confirm the region's aseismic setting. A more complete examination of late Quaternary continental margin stratigraphy will help resolve neotectonic and associated rheological problems, which have remained enigmatic in the absence or a stable datum.